An improved CRISPRi system in Pichia pastoris - Shujing Qiao; Fan Bai; Peng Cai; Yongjin J. Zhou; Lun Yao (Synthetic and Systems Biotechnology, 2023)
CRISPR interference (CRISPRi) has been developed and widely used for gene repression in various hosts. Here we report an improved CRISPRi system in Pichia pastoris by fusing dCas9 with endogenous transcriptional repressor domains. The CRISPRi system shows strong repression of eGFP, with the highest efficiency of 85%. Repression of native genes is demonstrated by targeting AOX1 promoter. AOX1 is efficiently repressed and the mutant strains show much slower growth in methanol medium. Effects of gRNA expression and processing on CRISPRi efficiency is also investigated. It is found that gRNA processing by HH/HDV ribozymes or Csy4 endoribonuclease generating clean gRNA is critical to achieve strong repression, and Csy4 cleavage shows higher repression efficiency. However, gRNA expression using native tRNA transcription and processing systems results in relatively weaker repression of eGFP. By expression of two gRNAs targeting promoters of eGFP and AOX1 in an array together with Cys4 recognition sites, both genes can be repressed simultaneously. Cys4-mediated gRNA array processing is further applied to repress fatty acyl-CoA synthetase genes (FAA1 and FAA2). Both genes are efficiently repressed, demonstrating that Cys4 endoribonuclease has the ability to cleave gRNAs array and can be can be used for multiplexed gene repression in P. pastoris.